Multidimensional Segments among Children in Urban Indian Families - Doke, Sunil Dhondopant; Bhola, Sarang Shankar (Indian Journal of Marketing, 2013)
A multidimensional segmentation procedure was run on 276 cases using Factor Analysis and Cluster Analysis that produced 24 segments among the children in urban India as per their user class of Lifestyle goods, Lifestyle, Personality and Media Exposure. A Discriminant Analysis was also conducted to predict whether children from urban families were influencing their parents’ purchase decisions of lifestyle goods or not. Predictor variables used for the Discriminant analysis are Self knowledge, Past influence, Newspaper preference, and Self driven score. Significant mean differences were observed for all the predictors on the DV. While the log determinants are quite similar, the discriminate function revealed a significant association between groups and all predictors, accounting for 78.85% of between group variability. The cross-validated classification showed that overall, 100% respondents were correctly classified. The study was carried out during 2008 to 2010.